The Influence Of Digital Tax Literacy On Formal Compliance Of Individual Taxpayers Following NIK-NPWP Integration - Mutiatus Shalihah; F Fauziyah; Ahmad Yani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research seeks to examine the extent to which digital tax literacy influences the formal compliance of individual taxpayers subsequent to the NIK-NPWP integration at the Kediri Pratama Tax Service Office. Employing a quantitative methodology with an explanatory design, cross-sectional data were gathered in December 2025 from 58 active taxpayer respondents who had successfully completed the NIK-NPWP matching process. The measurement instrument was subjected to validation through a pilot examination of 30 respondents (r-table = 0,361) and subsequently analyzed via simple linear regression utilizing SPSS version 27. Empirical findings confirm that digital tax literacy exerts a positive and statistically significant influence on formal compliance (t-count = 5,765 > t-table = 1,673; sig = 0,000; β = 0,497). The coefficient of determination R² = 0,372 reveals that 37,2% of the variance in formal compliance is attributable to digital tax literacy. These findings corroborate the integrative theoretical framework of the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM), explaining that digital tax literacy strengthens both the perceived usefulness and perceived ease of use of digital tax systems. The practical implications of this research highlight the critical need for a digital tax literacy program structured around four core dimensions: comprehension of NIK-NPWP regulatory provisions, proficiency in operating DGT Online and e-Filing platforms, cognizance of taxpayer rights and obligations, and technical problem-solving capabilities. Keywords: Digital Tax Literacy, Formal Compliance, NIK-NPWP, TPB, TAM